(untitled) (Innovaciones Educativas, 2020)
The purpose of this work is to propose a set of guidelines for the formulation of public policies aimed at the development of educational innovations in Latin America, based on the exploration of specialized literature, to determine the critical aspects of the development of innovations in the context Latin American. A selection of the documents was made based on the credibility of the sources, news, and relevance of the references. In the first part of the paper an introduction is presented on the problem of the gap in the relationship between society and education; factors that favor or hinder educational innovation are also analyzed; educational innovation in Latin America and its trends. In the second part, the following guidelines are proposed: build consensus, assume a systemic and contextualized vision, value educators, work in learning communities and take advantage of information and communication technologies. It is hoped that these guidelines will serve to: (a) formulate policies that guide and favor changes in education; (b) plan, develop and evaluate innovations in a more systematic, efficient and scientific way; and (c) contribute to generate a culture of educational innovation in Latin America.